PROCESSING AND IMPROVEMENT OF 2D SEISMIC DATA BY USING PRE-STACK AND POST-STACK TIME MIGRATION, KURDISTAN REGION, IRAQ - SULAIMAN, ZHIMAN FALAH; YOUSEF, BABAN MUSTAFA (Journal of Duhok University, 2023)
The accurate interpretation of seismic sections in areas with complex subsurface geology, presents numerous challenges including diffractions, inaccurate reflectors position, uncertain seismic amplitudes and noisy lateral discontinuities. Consequently the interpreter unable to construct and identify the subsurface geology from the seismic image. In order to create an accurate and illustrative subsurface image this study aimed in processing of one line of 2D raw reflection data, from Kurdistan region, northern of Iraq. The processing methodology consists of two main procedures, pre-stack and post-stack time migration. Different parameters are tested in all processing stages in order to compare and evaluate their efficiency in seismic data improvement. The results showed that the post-stack time migrated section showed great improvement of subsurface image comparing with stacked section without migration. While the pre-stack time migration presented better subsurface image